Benzenesulfonamides with benzimidazole moieties as inhibitors of carbonic anhydrases I, II, VII, XII and XIII. (February 2014) - Zubrienė, Asta; Čapkauskaitė, Edita; Gylytė, Joana; Kišonaitė, Miglė; Tumkevičius, Sigitas; Matulis, Daumantas
Abstract A series of benzenesulfonamide derivatives, bearing benzimidazole moieties, were designed and synthesized as inhibitors of carbonic anhydrases (CAs). Their binding affinities to recombinant human CA isozymes I, II, VII, XII and XIII were determined by the thermal shift assay. A group of compounds containing a benzimidazole substituent in the para position of the benzenesulfonamide ring was found to exhibit higher binding potency toward tested CAs than meta-substituted benzenesulfonamides. Some of these compounds exhibited nanomolar affinities and selectivity toward the CA isozymes tested.